RISKS OF GLAUCOMA TREATMENT IN PATIENTS WITH CATARACTS: A PROSPECTIVE COHORT STUDY - Kumar, Amrendra; Ambastha, Anita; Kumar, Vidya Bhushan (Student's Journal of Health Research Africa, 2024)
Background Glaucoma and cataracts frequently coexist in older adults, with glaucoma being a leading cause of irreversible blindness and cataracts contributing to reversible vision loss. Medical therapy for glaucoma primarily targets intraocular pressure (IOP) reduction, but its potential effects on cataract progression are not fully understood. This study assessed the risks associated with medical glaucoma therapy in patients with cataracts. Methods A total of 100 patients diagnosed with both glaucoma and cataracts were recruited. Baseline data included age, cataract severity, and IOP measurements. Patients were followed at 1, 3, and 6 months to assess cataract progression, visual acuity changes, and any side effects related to glaucoma treatment. Statistical analysis involved paired t-tests for intraocular pressure changes and Chi-square tests for cataract progression. Results: A total of 100 participants (56 males, 44 females) aged 40 years and older (mean age 65.4 ± 10.2 years) diagnosed with both glaucoma and cataracts were included. Thirty-five percent of participants experienced significant cataract progression, with those having more advanced baseline cataracts being at higher risk (p = 0.01). Mean IOP decreased significantly from 24.1 mmHg to 16.8 mmHg (p < 0.001) over the study period, indicating effective glaucoma control. Visual acuity worsened from 0.4 LogMAR to 0.6 LogMAR in patients with cataract progression (p = 0.02). Ocular side effects, such as dry eye and hyperemia, were reported in 25% of the cohort. Conclusion While medical therapy effectively controls IOP in glaucoma patients, it is correlated with an increased risk of cataract progression, particularly in those with severe cataracts at baseline. The decline in visual acuity highlights the need for careful monitoring of cataract status during glaucoma treatment. Recommendations Regular cataract progression monitoring and glaucoma medication adjustments may be needed for coexisting cataract patients. Alternative treatments include cataract and minimally invasive glaucoma operations may improve results.